Outpatients perspective : do cure and care 1Malaysia (C&C1M) Clinic Sungai Besi is effective or not? / Siti Zulaikha Mustapha, Nor Hafizah Mohamed Harith and Hardev Kaur Latchimanan - Mustapha, Siti Zulaikha; Mohamed Harith, Nor Hafizah; Latchimanan, Hardev Kaur (Universiti Teknologi MARA, Shah Alam, 2017)
Cure and Care 1Malaysia (C&C1M) Clinic is one of drug treatment and rehabilitation programmes introduced with the aims to provide drug treatment and rehabilitation through health approach as well as more humanistic, fun, effective and easy approach. This programme is part of the Government Transformation Program (GTP) introduced by the government in 2010. The establishment of C&C1M Clinic shows the changes in the trend of drug abuse and drug relapse among Malaysian. The statistic released by National Anti-Drug Agency (NADA) in 2013 indicates the increasing trends of the drug addiction in Malaysia, especially in Kuala Lumpur. This ponders more questions to the effectiveness of the drug treatment and rehabilitation program in Malaysia. Hence, this paper examines the effectiveness of drug treatment and rehabilitation program in C&C1M Clinic Sungai Besi and intention not to relapse among the receivers or the outpatient clients. This study adopted quantitative approach by using a case study involving n=46 outpatients at C&C1M Sungai Besi Kuala Lumpur. The findings of this study indicate that the level of effectiveness of C&C1M Clinic Sungai Besi, Kuala Lumpur from the perspective of the clients was high (Mean=4.455; Std. Dev. 0.569). This study has revealed there was a significant relationship between the effectiveness of drug treatment and rehabilitation program towards intention not to relapse among the outpatient clients r=0.576 and p< 0.00. Hence, this study concludes that the health approach in C&C1M clinic gives huge impact towards the life of outpatients.